An fMRI Investigation of Analogical Mapping in Metaphor Comprehension: The Influence of Context and Individual Cognitive Capacities on Processing Demands - Prat, Chantel S. (2011)
This study used fMRI to investigate the neural correlates of analogical mapping during metaphor comprehension, with a focus on dynamic configuration of neural networks with changing processing demands and individual abilities. Participants with varying vocabulary sizes and working memory capacities read 3-sentence passages ending in nominal critical utterances of the form “X is a Y.” Processing demands were manipulated by varying preceding contexts. Three figurative conditions manipulated difficulty by varying the extent to which preceding contexts mentioned relevant semantic features for relating the vehicle and topic of the critical utterance to one another. In the easy condition, supporting information was mentioned. In the neutral condition, no relevant information was mentioned. In the most difficult condition, opposite features were mentioned, resulting in an ironic interpretation of the critical utterance. A fourth, literal condition included context that supported a literal interpretation of the critical utterance. Activation in lateral and medial frontal regions increased with increasing contextual difficulty. Lower vocabulary readers also had greater activation across conditions in the right inferior frontal gyrus. In addition, volumetric analyses showed increased right temporo-parietal junction and superior medial frontal activation for all figurative conditions over the literal condition. The results from this experiment imply that the cortical regions are dynamically recruited in language comprehension as a function of the processing demands of a task. Individual differences in cognitive capacities were also associated with differences in recruitment and modulation of working memory and executive function regions, highlighting the overlapping computations in metaphor comprehension and general thinking and reasoning.